FREQUENCY OF AWARENESS IN MOTHERS ABOUT RISK FACTOR OF ASTHMA IN 1 TO 12 YEARS OLD CHILDREN - Ahmad, Sagheer; Malik, Qudratullah; Chatha, Mazhar Nazir; Hussain, Abdul Wahid; Abbas, Muhammad; ., Aurangzeb (Pakistan Armed Forces Medical Journal, 2018)
Objective: To determine the frequency of awareness in mothers about the risk factors of asthma in children aged 1-12 years, attending pediatric department, Combined Military Hospital, Quetta.Study Design: Descriptive, cross sectional study.Place and Duration of Study: The study was conducted at department of Pediatrics, Combined Military Hospital Quetta. Duration of the study was six months from Oct 2011 to Apr 2012. Material and Methods: All the mothers of children with asthma were selected for this study. Informed consent was taken from all the patient’s parents participated in the study. Every patient was assigned a serial number. Detailed history about risk factors was taken by the researcher and all the information entered in the proforma and collected data was analyzed by SPSS version 22. Results: Total 150 mothers were included in study. There were 9 (6.0%) mothers who had awareness of any relation between breast feed and the risk of asthma in children, 15 (10%) mother had awareness of relation between pet animals / birds and the risk of asthma in children, 3 (2%) mothers had awareness of relation between carpets at home and the risk of asthma, 24 (16%) mothers had awareness of relation between cigarette smoke and the risk of asthma in children. There were 15 (10%) mothers who had awareness about relation between food and the risk of asthma, 3 (2%) mother had awareness of relation between repeated use of medicines in children under six months of age and the risk of asthma, 5 (3.3%) mothers had awareness of relation between the use of pillows and the risk of asthma, 3 (2%) mothers had awareness of relation between the presence of cockroaches in child’s bedroom and the risk of asthma in children. Conclusion: In Quetta region, mothers had lower frequency of awareness among mothers regarding pediatric (112 years) asthma development and its associated risk factors.